2010
DOI: 10.1007/s12394-010-0045-z
|View full text |Cite
|
Sign up to set email alerts
|

Built-in privacy—no panacea, but a necessary condition for effective privacy protection

Abstract: Built-in privacy has for too long been neglected by regulators. They have concentrated on reacting to violations of rules. Even imposing severe fines will however not address the basic issue that preventative privacy protection is much more meaningful. The paper discusses this in the context of the International Working Group on Data Protection in Telecommunications ("Berlin Group") which has published numerous recommendations on privacy-compliant design of technical innovations. Social network services, road … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A broader privacy approach is necessary. We have shown that PbD with its tech-based solutions is no panacea because there is no simple fix for complex privacy challenges (Dix, 2010;Hartzog, 2018). Whilst companies have an interest in ensuring the employee productivity and preventing misconduct in the workplace, the measures to uphold that interest do not justify extensively invasive practices for quantifying the social modes of interaction and connected performance goals (Ajunwa et al, 2017).…”
Section: Legal Protection Of Employee Privacy At the Workplacementioning
confidence: 99%
See 1 more Smart Citation
“…A broader privacy approach is necessary. We have shown that PbD with its tech-based solutions is no panacea because there is no simple fix for complex privacy challenges (Dix, 2010;Hartzog, 2018). Whilst companies have an interest in ensuring the employee productivity and preventing misconduct in the workplace, the measures to uphold that interest do not justify extensively invasive practices for quantifying the social modes of interaction and connected performance goals (Ajunwa et al, 2017).…”
Section: Legal Protection Of Employee Privacy At the Workplacementioning
confidence: 99%
“…The expectations for PbD from scholars from different continents and disciplines are high: PbD is described as a pragmatic compliance enabler to guarantee important elements of procedural regularity (Kroll et al., 2017; McQuay and Cavoukian, 2010). Some scholars claim that it will be difficult if not impossible to achieve meaningful privacy protection in the 21st century without PbD (Dix, 2010). Indeed, design-based approaches are popular even beyond the tech industry and have increasingly found their way into legal frameworks.…”
Section: Existing Framework For the Protection Of Employee Privacy At The Workplacementioning
confidence: 99%